MONITORING COASTLINE CHANGE IN THE RED RIVER DELTA USING REMOTELY SENSED DATA - Thao, Nguyen Van; Thanh, Tran Duc; Saito, Yoshiky; Gouramanis, Chris (Vietnam Journal of Marine Science and Technology, 2014)
This study focuses on the use of remotely sensed data for monitoring coastline changes in the Red River Delta during the 1998 to 2008 period. For the satellite image data processing, the shoreline was defined as the mean sea level on the muddy coast where the tide is the dominant dynamic factor and as the mean high sea level on the sandy coast where the ocean waves are the dominant dynamic factor. A GIS approach was used for the quantitative analysis of coastline change. It was observed that the coastline change in the Red River Delta underwent complicated changes during this 10 year period. In this period, the accretion rate in Red River Delta coastal area was about 10,256ha and the erosion rate was about 542ha. In the Hai Hau and Hau Loc coastal areas, erosion occurred in a large scale and was very intense. Along other coastlines of the Red River Delta, sediment accretion dominated at rates of over 30m/year. These zones of varying erosion and accretion have important implications for coastal zone management in the Red River Delta region.